RETHINKING THE CONCEPTUAL FOUNDATIONS OF KERALA'S DECENTRALIZATIONIN THE LIGHT OF THE EXPERIENCE DURING THE PAST DECADE - V. Santhakumar (Centre for Development Studies- RESEARCH AND POLICY NOTE No. 3, 2008)
Though the decade-long decentralization in Kerala has made remarkable achievements in terms of consistent devolution of financial resources, and improvement in the implementation of poverty eradication schemes, there are many glaring limitations.These include the tendency to take up many unviable projects, lack of proper monitoring and evaluation, inadequate functioning of grama sabhas and beneficiary committees, continuing lethargy in service delivery, very slow progress in computerization, etc. In this context, this note makes an outline of a more realistic conceptual foundation for decentralization. It calls for using the concept of `localmarket failure' in deciding the activities of LSG, treating grama sabhas and beneficiary committees as mechanisms to exercise citizens' rights in extreme or emergency situations, enhancing local resource mobilization, and instituting incentive systems so that localresource allocation becomes both autonomous and efficient